Proteomic Characterization of Human Gut Habitual Bacteroides intestinalis against Common Intestinal Bile Acid Stress - Sun, Zeyu; Wang, Yu; Su, Xiaoling; Yang, Xue; Luo, Qixia (Advanced Gut & Microbiome Research, 2023)
Bacteroides intestinalis (B. intestinalis) is an abundant gastrointestinal commensal bacterium and is able to produce secondary bile acids (BAs) among other important metabolic functions. However, deoxycholic acid (DCA) is known to suppress Bacteroides, suggesting differential molecular impact of different BA species on Bacteroides. Among major human gastrointestinal BA components, we first demonstrated that DCA and chenodeoxycholic acid (CDCA) and their taurine-conjugated species at 1 mM showed significantly higher inhibitory effects on the growth of B. intestinalis than cholic acid (CA) and lithocholic acid (LCA) and their taurine-conjugated species. Then, high-throughput proteomic strategy was used to show that both TCDCA and TDCA caused more proteome-wide modulation than TCA and TLCA. In response to incremental BA toxicity, the main functional changes of B. intestinalis include enhanced protein synthesis, DNA integrity maintenance, and suppressed central metabolic activities. Importantly, key energy and BA metabolism enzymes of B. intestinalis were inhibited by TCDCA and TDCA. These findings provide a basis for future studies to explore how Bacteroides respond to bile stress and how BA composition modulate gut microbiome homeostasis.